Green roof as an effective tool for sustainable urban development: An Australian perspective in relation to stormwater and building energy management. (15th August 2022) - Alim, Mohammad A.; Rahman, Ataur; Tao, Zhong; Garner, Brad; Griffith, Robert; Liebman, Mark
Abstract: Green infrastructure could provide a suite of benefits, including stormwater management and climate change impact mitigation. While European countries, the USA and Canada are increasingly adopting green roofs, Australia is lagging behind. This study specifically reviews the performance of green roofs in terms of stormwater retention, runoff quality, building energy consumption and life cycle cost analysis, as well as policy development in the Australian context. Research studies on these topics within Australia are identified, collated and analysed with respect to other studies reported by reputable research groups in other countries, where the green roof system has already matured. It should be mentioned that the results related to energy consumption were from simulation studies and empirical evidence derived from limited case studies, as reported in the literature. This study found that the average water retention capacity (worldwide) of a green roof is around 66.2%, which is within to the values (60–70%) reported in Australian studies. Because of the high water retention capacity, green roofs limit the export of pollution for most storm events. But when green roofs are saturated, they may be a source of pollution. However, the concentration of the pollutant decreases significantly over time. The temperature reduction by green roofs in buildings ranges between 4 and 6 °C. There is a potential for energy savings in building heating and cooling, but the findings from the literature are highly variable (ranges between 9 and 50%). The average payback period reported for a green roof is about 16 years. However, this depends on the initial cost, maintenance and assumed discount rate in the study. It has been shown that government policies and public awareness are important to increase the green roof adoption rate. Finally, current challenges in adopting this technology and future research directions are summarised. Highlights: Average water retention capacity of a green roof is around 66.2%. When green roofs are saturated, they may be a source of pollution. Temperature reduction by green roofs in buildings ranges between 4 and 6 °C. Average payback period reported for a green roof is about 16 years.